LANGUAGE STYLES WITHIN TRANSLANGUAGING IN DEDDY CORBUZIER'S PODCAST WITH VINCENT VERHAAG AND EL BARACK - Laela Kamalina Witra; Rohmani Nur Indah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Nowadays, one of the prerequisites for the virality of podcasts on social media is determined by the host's expertise in guiding the show by using the right language style and language choice. Research in the field of language style and language choice still explores the dynamics of conversation without looking at the application of translanguaging. Therefore, research is needed that combines translanguaging and language style in the context of social media. This research explores the relationship between translanguaging and language style in one of the episodes of Deddy Corbuzier's podcast with guests Vincent Verhaag and El Barack. The podcast received many viewers and likes, as well as a lot of positive comments. This research refers to the theory of language style to analyze how speakers adjust their language choices in a multicultural environment to achieve various communication goals. The approach used is descriptive qualitative, transcribing and analyzing data in the form of dialogues that appear in the podcast. The research results show the presence of seven translanguaging patterns, with the Indonesian to Code-Mixing (ICM) pattern being the most dominant, reflecting the natural integration of languages in informal conversations. In addition, the dynamics of language change were also found, indicating three types of language styles as described by Martin Joos. The most dominant language style is the casual style, followed by the Consultative Style and the Intimate Style. It can be concluded that this study indicates that language speakers adjust their speech style based on the audience, the topic being discussed, and the communication goals they wish to achieve. This research will help readers gain deeper insights into multilingual communication, particularly in the realm of digital media which shows that translanguaging can be used strategically to enhance clarity, emotional expression, and audience engagement.